2021
DOI: 10.1088/1555-6611/abece0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of laser-activated bleaching with 445 nm and 970 nm diode lasers on pulp chamber temperature rise: an in vitro study

Abstract: The aim of this study was to determine the pulp chamber temperature changes during bleaching procedures with irradiation from 445 nm and 970 nm diode lasers at different powers. A total of 120 human maxillary central incisors were used for this study. Diode lasers at two different wavelengths were irradiated in this evaluation: 970 nm at 1.5 W of power, 970 nm at 2 W, 445 nm at 1 W and 445 nm at 1.5 W. A thermometer was inserted into the pulp chamber and the temperature increase after bleaching was recorded. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The 2023 study found that an average power of a diode laser (445 nm) of 0.5-2 W and an irradiation time of 10-60 s can be considered safe for pulp health when a red-colored bleaching gel is used [31]. The 2021 study found that the temperature rise of the pulp after bleaching with the diode laser was within the safe range at a wavelength of 970 nm and a power of 1.5 W and 2 W and at 445 nm and a power of 1 W and 1.5 W. The highest temperature rise of the pulp was observed with the diode laser at a wavelength of 970 nm and a power of 2 W (2.0 ± 0.5), while the lowest temperature rise of the pulp (0.1 ± 0.2) was observed with the diode laser at a wavelength of 445 nm and a power of 1 W [32]. Due to the high absorption in hemoglobin and melanin [33], a laser wavelength of 445 nm is mainly used in oral surgery [34].…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…The 2023 study found that an average power of a diode laser (445 nm) of 0.5-2 W and an irradiation time of 10-60 s can be considered safe for pulp health when a red-colored bleaching gel is used [31]. The 2021 study found that the temperature rise of the pulp after bleaching with the diode laser was within the safe range at a wavelength of 970 nm and a power of 1.5 W and 2 W and at 445 nm and a power of 1 W and 1.5 W. The highest temperature rise of the pulp was observed with the diode laser at a wavelength of 970 nm and a power of 2 W (2.0 ± 0.5), while the lowest temperature rise of the pulp (0.1 ± 0.2) was observed with the diode laser at a wavelength of 445 nm and a power of 1 W [32]. Due to the high absorption in hemoglobin and melanin [33], a laser wavelength of 445 nm is mainly used in oral surgery [34].…”
Section: Introductionmentioning
confidence: 90%
“…The thermal effect was investigated in the following test groups, each of them consisting of 15 teeth. The laser settings are determined by preliminary tests and studies [28,31,32] or by following the manufacturer's instructions: Body temperature (36.5 ± 1.5 • C), which was confirmed via the thermocouples, was set before data collection. The setting was made using the heated water bath.…”
Section: Investigation Of the Thermal Effectmentioning
confidence: 99%
See 3 more Smart Citations